ПАРАМЕТРИ ЛІНГВОКУЛЬТУРНОЇ КОМПЕТЕНЦІЇ МОВНОЇ ОСОБИСТОСТІ - Торосян О. М.; Шелякіна А. В. (World Science, 2019)
The given article considers the problems within linguacultural studies. It is aimed to determine the peculiarities of the linguistic personality. Different approaches to this problem are analyzed concerning the parameters of the linguistic personality. Linguacultural competence is considered to be an integral part of general linguistic competence and important factor for successful communicative activity of the linguistic personality.